PENGUJIAN APLIKASI PURCHASE ORDER BARANG BERBASIS WEB ONLINE DENGAN METODE WATERFALL STUDY KASUS PADA CV AGROLUWI LESTARI - Fandy Maulana; Muhamad Agel Rozali; Muhamad Dwiky Finastika Watimen; Sukma Manggar Suci Putri; Aries Saifudin (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2023)
In the current era of globalization, technology continues to develop, marketing departments can apply a new technology, quickly and are able to reach globally in a short time and with efficient funds. CV Agroluwih Lestari is one of the MSMEs (Micro, Small and Medium Enterprises) engaged in the needs of groceries, fruits, spices and other needs. Previously, these MSMEs still used a manual system where orders were only via WhatsApp which was then made a Purchase Order or known as a PO. This study aims to design and build a purchase order application or system that complies with the requirements of these SMEs. The application system is built using the PHP Framework system and the PHP Mysql database. In this practical work the author also uses the Waterfall web-based software design method. The following are the stages carried out by the author in practical work using the waterfall model as software development, namely requirements analysis, design, implementation, integration & testing, verification, and operation & maintenance. From the results of the discussion and testing of the Purchase Order application using the User Acceptance Test that has been carried out, several conclusions are drawn from the research including the system has been able to provide convenience to CV Agroluwi Lestari in terms of ordering goods, this is evidenced by the UAT test results of 80% which includes into the strongly agree category.